Effect of Herbal Extracts of Bryophyllum calycinum and Achyranthes aspera on Serum Biochemical Profile of Rats Having Adenine Induced Chronic Kidney Disease - Gehani, Mukesh T; Raval, SK; Panchal, MT; Rao, Neha (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
The experiment was undertaken to study the therapeutic efficacy of aqueous and alcoholic extracts of Bryophyllum calycinum and  Achyranthes aspera on adenine induced chronic kidney disease (CKD) in male Wistar rats. The rats (n = 48) were divided randomly into  eight equal groups (n = 6 each). Group I and II served as normal and adenine control, respectively. In group II to VIII, CKD was induced  by administration of adenine (200 mg/kg) along with drinking water for 28 days. After 28th day, the rats of CKD induced Groups III to VIII  were given aqueous and alcoholic plant extracts of B. calycinum and A. aspera @ 300 mg/kg b.wt. orally as either single or combination  of both herbal extracts (3:1) in 0.5 % sodium bicarbonate using syringe and rat gavage needle. CKD was confirmed by evaluating serum  biochemical parameters before and after herbal treatment. Increased levels of serum glutamic pyruvic transaminase, urea nitrogen,  uric acid, creatinine and phosphorus, while decreased levels of serum total protein were observed in all CKD groups by 28th day as  compared to 0 day or normal control group, which was significantly reverted to near normal levels by day 70th following administration  of single aqueous/alcoholic extract or a combination as biherbal extracts (3:1) from day 28 to 70 of experiment. The serum albumin and  calcium, however, did not show significant alteration in any of the groups. Results of serum biochemistry revealed that aqueous and  alcoholic extracts of B. calycinum and A. aspera possess good therapeutic/nephroprotective efficacy against CKD. The effect of biherbal  alcoholic extract of the plants was much better in restoring the biochemical values of CKD induced rats by 42 days of administration.
Keywords: Achyranthe saspera; Bryophyllum calycinum; Herbal extracts; Nephroprotective effect; Serum biochemistry; Wistar rats